Festival cities - Gold, John R.,Gold, Margaret M. (Routledge, 2020)
Introduction – Ancient and modern – Biennale – Salzburg – Cannes – Edinburgh – Proliferation – Asserting identity – Conclusion.
10.4324/9781003130802
Keywords: Festivals; City planning; City promotion; Place marketing; Stadt; Kulturpolitik; Festival; Konzeption; Motivation; Stadtplanung; Einflussgröße; Interesse; Soziokultureller Faktor; Funktion; Potenzial; Management; Marketing; ARCHITECTURE / Landscape; ARCHITECTURE / Urban & Land Use Planning; SOCIAL SCIENCE / Popular Culture